The Impact of Tax, Exchange Rate, Tunneling Incentive and Firm Size on Transfer Pricing (Empirical Study of Manufacturing Companies Listed on the Indonesian Stock Exchange for Years2014-2018): English - Wijaya, Felicia Vanessa; Widianingsih, Luky Patricia (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2019)
Abstract: In the era of globalization, companies are developing into multinational companies that establish branches or subsidiaries in various countries. This globalization has given an impact to increase international transaction. These transactions could lead to transactions with related parties that shows an indication of transfer pricing. Along with the development of globalization, factors affecting transfer pricing are not only derived from taxes, but also from other factors. The purpose of this research is to examine the effect of tax, exchange rate, tunneling incentive, and firm size on transfer pricing. This research used secondary data in the form of annual reports published on the Indonesia Stock Exchange. Population of this research was manufacturing companies for years 2014-2018 and by purposive sampling method, a sample of 19 manufacturing companies was obtained. Analysis technique used on this research was a multiple linear regression using SPSS 23 application. The result shows that tax, tunneling incentive, firm size have significant effect on transfer pricing, while exchange rate does not take any effect on transfer pricing. Adjusted R2 determination coefficient of 32,8% shows transfer pricing is affected by tax, exchange rate, tunneling incentive, and firm size, while remaining 67,2% is affected by other variables outside research model. Keywords: Transfer Pricing; Tax; Exchange Rate; Tunneling Incentive; Firm Size.